Appropriate Shocks and Mortality in Patients With Versus Without Diabetes With Prophylactic Implantable Cardioverter Defibrillators - Junttila, M Juhani; Pelli, Ari; Kenttä, Tuomas V; Friede, Tim; Willems, Rik; Bergau, Leonard; Malik, Marek; Vandenberk, Bert; Vos, Marc A; Schmidt, Georg; Merkely, Bela; Lubinski, Andrzej; et al. (Diabetes care, 2020)
Diabetes increases the risk of all-cause mortality and sudden cardiac death (SCD). The exact mechanisms leading to sudden death in diabetes are not well known. We compared the incidence of appropriate shocks and mortality in patients with versus without diabetes with a prophylactic implantable cardioverter defibrillator (ICD) included in the retrospective EU-CERT-ICD registry. A total of 3,535 patients from 12 European EU-CERT-ICD centers with a mean age of 63.7 ± 11.2 years (82% males) at the time of ICD implantation were included in the analysis. A total of 995 patients (28%) had a history of diabetes. All patients had an ICD implanted for primary SCD prevention. End points were appropriate shock and all-cause mortality. Mean follow-up time was 3.2 ± 2.3 years. Diabetes was associated with a lower risk of appropriate shocks (adjusted hazard ratio [HR] 0.77 [95% CI 0.62-0.96], = 0.02). However, patients with diabetes had significantly higher mortality (adjusted HR 1.30 [95% CI 1.11-1.53], = 0.001). All-cause mortality is higher in patients with diabetes than in patients without diabetes with primary prophylactic ICDs. Subsequently, patients with diabetes have a lower incidence of appropriate ICD shocks, indicating that the excess mortality might not be caused primarily by ventricular tachyarrhythmias. These findings suggest a limitation of the potential of prophylactic ICD therapy to improve survival in patients with diabetes with impaired left ventricular function.